Determination of the stability of veterinary cream containing silver citrate - Polova, Zhanna (ScienceRise: Pharmaceutical Science, 2017)
An innovative activity in the field of development of new Ukrainian medicines for veterinary pharmacy remains relevant. The problem of treatment and prevention of mastitis in cows in Ukraine is not resolved. Almost all anti-mastitis drugs available on the market are antibiotics, which exacerbates the existing problem of antibiotic resistance, the solution of which is possible due to the development of new veterinary drugs with minimal side effects and maximum therapeutic efficacy. Aim. The aim of the research was to study the stability of the silver citrate containing veterinary drug consisting of the soft dosage form with antimicrobial activity codenamed "Argocid K". Methods. Pharmaco-technological, physico-chemical, and microbiological methods of research were carried out in accordance with the requirements of the State Pharmacopoeia of Ukraine. Results. The study of the stability of samples of cream "Argocid K" was carried out on five series of remedies, packed in aluminium tubes with internal lacquer coating and orange glass jars every 6 months within 27 months. Shelf life of the cream was determined at two temperature regimes - under room conditions (15–25) °C and in a cool place at (8–15) °C. In result of the study it was determined that all series of samples of the veterinary cream "Argocid K" satisfy requirements of the tests concerning thermal and colloidal stability. The quantitative content of the ions of the silver was determined using thiocyanometric titration method. The quantitative determination of dexpanthenol was carried out by liquid chromatography. The obtained data point to the stability of the drug. Microbiological studies have shown that the degree of microbial contamination of the drug meets the requirements of the State Pharmacopoeia of Ukraine for topical preparations. Silver citrate, which is included into the cream, shows a preservative effect in the studied concentration. Conclusion. The shelf life of the cream, in particular, 2 years and 3 months was determined. The results show the opportunity to predict the shelf life of the drug within two years and 3 months at a temperature of 8–25 °C and may be taken into account during development of the Draft of quality control methods for the cream "Argocid K" for its use in veterinary medicine